DESTILASI MINYAK ATSIRI DAUN SURIAN SEBAGAI KRIM PENCEGAH GIGITAN NYAMUK Aedes aegypty L. (Makara Journal of Science, 2011)
Distillation of Essential Oil from Surian Leaf (Toona sureni (Bl.) Merr.) as Repellent Cream for Protection Aedes aegypty L. Bites. Isolation of volatile oil of leaf surian (Toona sureni (Bl.) Merr.) have been done by distillation aqueous vapour method. Distillation result had the chocolate colored and stinging aroma, and rendement was 0.23%. GC-MS analysis shown of some compound of terpenoid (naftalen derivated) which correspondence to mass spectrum. One of them is copaene (C15H24), m/z = 204. Cream based of Rajin et al. formula giving stable cream, white coloured and neutral pH. Volatile oil of surian leaf in cream based cause color and aroma cream were changed. Cream stability also was annoyed at oil of atsiri 10%.